Environment-friendly material for outdoor seat and production process of environment-friendly material

By using functional fiber fillers and branched polyamide amine structures in outdoor seating materials, the problem of insufficient UV resistance and antibacterial and mildew resistance of polylactic acid materials is solved, and the mechanical properties and service life of the material are significantly improved.

CN119161707AInactive Publication Date: 2024-12-20ZHEJIANG FEIYI INTELLIGENT EQUIP CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411678821.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing outdoor seating materials such as polyethylene and polypropylene are not environmentally friendly and degradable. The polylactic acid materials have poor UV resistance, insufficient toughness, and insufficient antibacterial and mildew resistance, resulting in aging of the material and short service life.

Method used

70-90 parts of polylactic acid, 20-50 parts of polycarbonate, 2-5 parts of compatibilizer, 1-4 parts of lubricant, 1-3 parts of antioxidant, 3-6 parts of functional fiber filler, 2-5 The combination of antibacterial and anti-mold components is enhanced by modifying quartz fiber and branched polyamide amine structure, improving the resistance to UV, impact toughness and anti-bacterial and anti-mold properties.

Benefits of technology

It significantly improves the material's UV resistance, impact toughness and antibacterial and mildew resistance, extends the service life of outdoor seats, and enhances the mechanical properties and durability of environmentally friendly materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161707A_ABST
    Figure CN119161707A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, and discloses an environment-friendly material for outdoor seats and a production process thereof.The environment-friendly material is prepared from polylactic acid, polycarbonate, a compatilizer, a lubricant, an antioxidant, functional fiber filler and an antibacterial and mildewproof component. The mechanical property and the ultraviolet resistance of the environment-friendly material can be improved, and the influence on the performance of the environment-friendly material due to aging caused by long-term ultraviolet irradiation in an outdoor environment is avoided; by adding the antibacterial and mildew-proof component, the impact toughness and antibacterial and mildew-proof performance of the environment-friendly material are enhanced, and the outdoor seat prepared from the environment-friendly material can have excellent mechanical properties, impact toughness, ultraviolet resistance and antibacterial and mildew-proof performance, can keep stable performance under long-term outdoor use conditions, and is long in service life and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to an environmentally friendly material for outdoor seats and a production process thereof. Background Art

[0002] Outdoor chairs provide people with a place to rest and relax outdoors, meeting people's various needs for working, studying, resting, holding activities, etc. outdoors. Outdoor chairs made of plastic as the main material have the advantages of light weight and diverse designs, and can meet the use needs of various outdoor environments. Common plastic materials used to manufacture outdoor chairs include polyethylene (PE), polypropylene (PP), polycarbonate (PC), acrylonitrile-butadiene-styrene copolymer (ABS) materials, etc., which have the advantages of light texture, durability, easy cleaning, not easy to deform, strong impact resistance, etc. However, these plastic materials are traditional petroleum-based materials, consume natural resources, and are not environmentally friendly and degradable. Outdoor chairs are usually used for a long time. During use, petroleum-based materials will continuously interact with the environment, produce harmful substances that pollute the soil and air, and waste will burden the environment. Therefore, research and improvement of environmentally friendly materials used to make outdoor chairs are of great practical significance.

[0003] Polylactic acid (PLA) is a bio-based, environmentally friendly and degradable material that can be completely degraded into carbon dioxide and water. It has excellent properties such as non-toxicity, low density, easy processing, wear resistance and water resistance, and can be used to make outdoor chairs. However, the performance of PLA materials still has shortcomings, which limits the application of PLA materials. PLA materials have poor UV resistance. Under long-term ultraviolet irradiation, the molecular chain is easily broken, resulting in material aging and performance degradation; PLA materials have poor toughness and are easily damaged when impacted by external forces; in addition, the antibacterial and mildew-proof properties of PLA also affect the health of users and the service life of outdoor chairs. Improving the antibacterial and mildew-proof properties of PLA materials can effectively reduce the erosion of microorganisms such as bacteria and mold on the material, reduce the frequency of cleaning and maintenance, and increase the service life of the material. Therefore, the present invention provides an environmentally friendly material with PLA as a matrix, excellent performance, and a long service life, which can be used to make outdoor chairs. Summary of the invention

[0004] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide an environmentally friendly material for outdoor chairs and a production process thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: An environmentally friendly material for outdoor seats comprises the following raw materials in parts by weight: 70-90 parts of polylactic acid, 20-50 parts of polycarbonate, 2-5 parts of a compatibilizer, 1-4 parts of a lubricant, 1-3 parts of an antioxidant, 3-6 parts of a functional fiber filler, and 2-5 parts of an antibacterial and anti-mildew component.

[0006] Furthermore, the compatibilizer is ethylene-methyl acrylate-glycidyl methacrylate; the lubricant is polyethylene wax; and the antioxidant is antioxidant 1010 or antioxidant 168.

[0007] Furthermore, the method for preparing the functional fiber filler comprises the following steps: S1. Mix quartz fiber with N,N-dimethylformamide, raise the temperature to 60-80°C, add chloroethyl isocyanate and catalyst A, react for 2-4 hours, filter, wash and dry to obtain modified quartz fiber; S2. Add the modified quartz fiber into toluene, mix well, introduce nitrogen, raise the temperature to 70-80°C, add 2,2,6,6-tetramethyl-4-piperidinol and an alkaline catalyst, react for 3-5 hours, filter, wash and dry to obtain a functional fiber filler.

[0008] By adopting the above technical scheme, under the action of a catalyst, the hydroxyl groups on the surface of the quartz fiber can react with the isocyanate in the structure of chloroethyl isocyanate, thereby introducing chlorine substituents on the surface of the quartz fiber to obtain modified quartz fiber. Under the action of an acid binding agent, the chlorine substituents on the surface of the modified quartz fiber can undergo a substitution reaction with the hydroxyl groups in the structure of 2,2,6,6-tetramethyl-4-piperidinol to obtain a functional fiber filler.

[0009] Furthermore, in S1, the catalyst A is dibutyltin dilaurate or stannous octoate.

[0010] Furthermore, in S2, the alkaline catalyst is a sodium carbonate solution or a potassium carbonate solution.

[0011] Furthermore, the preparation method of the antibacterial and mildew-proof component is as follows: Add polyamide amine to toluene and stir evenly, add anhydride modifier, react at room temperature for 1-3 hours, then increase the temperature to 80-100°C, add diniconazole and catalyst B, keep the temperature for 3-5 hours, cool to room temperature, discharge and obtain antibacterial and antifungal components.

[0012] By adopting the above technical scheme, the amino group in the polyamide amine structure can react with the anhydride modifier, thereby introducing a carboxyl group into the structure. Under the action of catalyst B, the carboxyl group can undergo an esterification reaction with the hydroxyl group in the diniconazole structure to obtain an antibacterial and antifungal component.

[0013] Furthermore, the acid anhydride modifier is succinic anhydride or glutaric anhydride.

[0014] Furthermore, the catalyst B is p-toluenesulfonic acid.

[0015] A production process of environmentally friendly materials for outdoor seats, comprising the following steps: Step 1: Add polylactic acid, polycarbonate, compatibilizer, lubricant, antioxidant, functional fiber filler, and antibacterial and mildew-proof components into a high-speed mixer, raise the temperature to 60-90° C., and mix for 1-2 hours to obtain a premix; Step 2: placing the premix in a twin-screw extruder, melt-extruding and granulating to obtain an environmentally friendly material.

[0016] Furthermore, in step 2, the extrusion temperature of the twin-screw extruder is 180-220° C., and the screw speed is 100-400 r / min.

[0017] Beneficial effects of the present invention: (1) The functional fiber filler prepared by the present invention takes quartz fiber as the matrix. After the quartz fiber is organically modified, the compatibility problem between the quartz fiber and the polylactic acid matrix is ​​improved. The functional fiber filler can be evenly dispersed in the polylactic acid matrix, and the interface bonding effect with the polylactic acid matrix is ​​further enhanced. The functional fiber filler plays a reinforcing role in the polylactic acid matrix and improves the mechanical properties of the polylactic acid matrix. In addition, the surface of the functional fiber filler is grafted with small molecules containing hindered amine groups, which can avoid the migration and precipitation of small molecule anti-ultraviolet agents, and can act in the polylactic acid matrix for a long time, thereby enhancing the anti-ultraviolet performance of environmentally friendly materials, and preventing environmentally friendly materials from being irradiated by ultraviolet rays for a long time in outdoor environments, causing aging, resulting in a decrease in the performance of environmentally friendly materials, and affecting the service life of outdoor seats.

[0018] (2) The antibacterial and mildew-proof component prepared by the present invention contains a branched polyamide amine, which has a large number of amide bonds in its branched structure, and can interact with the molecular chain groups of the polylactic acid matrix, increase the entanglement between the polylactic acid molecular chains, promote the crystallization nucleation of the system, and improve the crystallization rate of the system. At the same time, it enhances the density of the polylactic acid matrix, can effectively disperse and transmit stress, enhance the impact toughness of the polylactic acid matrix, prevent the material from being damaged when subjected to external impact, and improve the impact toughness of the environmentally friendly material. The small molecule antibacterial and mildew-proof substance dinazole has a high-efficiency and broad-spectrum antibacterial and mildew-proof effect. After chemically bonding with the polyamide amine, it can act for a long time in the polylactic acid matrix, effectively enhancing the antibacterial and mildew-proof performance of the environmentally friendly material, and can also avoid the migration and precipitation of small molecule antibacterial and mildew-proof substances, and avoid the erosion of environmentally friendly materials by microorganisms such as bacteria and molds, thereby extending the service life of outdoor chairs.

[0019] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0021] Figure 1 This is the infrared spectrum of the functional fiber filler prepared by the present invention; Figure 2 This is the infrared spectrum of the antibacterial and mildew-proof component prepared by the present invention. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The preparation methods of the functional fiber fillers and antibacterial and antifungal components in the following examples and comparative examples are as follows: Preparation of functional fiber fillers S1. Mix 3.2 g of quartz fiber with N,N-dimethylformamide, raise the temperature to 70°C, add 2.6 g of chloroethyl isocyanate and 0.2 g of dibutyltin dilaurate, react for 3 h, filter, wash and dry to obtain modified quartz fiber; S2. Add 2.8 g of modified quartz fiber into toluene, mix well, introduce nitrogen, raise the temperature to 75°C, add 2 g of 2,2,6,6-tetramethyl-4-piperidinol and 0.3 g of potassium carbonate solution, react for 4 hours, filter, wash and dry to obtain a functional fiber filler.

[0024] The sample was prepared by potassium bromide tableting method, and the functional fiber filler was tested by infrared spectrometer AVATAR-370FT. Figure 1 As shown in the figure, analysis shows that in the infrared spectrum of functional fiber fillers, 1709cm -1 The absorption peak of C=O in carbamate appeared at 1540 cm -1 The absorption peak of NH in carbamate appeared at 1465 cm -1 、1383cm -1 、1366cm -1 The absorption peak of piperidine ring appeared at 1132 cm-1 The absorption peak of ether bond CO appeared at 1086 cm -1 The absorption peak of Si-O-Si appears.

[0025] Preparation of antibacterial and antifungal components 6 g of polyamide amine was added to toluene and stirred evenly, 2.2 g of succinic anhydride was added, and the reaction was carried out at room temperature for 2 hours. The temperature was then raised to 95°C, 1.6 g of oxadiazole and 0.5 g of p-toluenesulfonic acid were added, and the reaction was kept warm for 5 hours. After cooling to room temperature, the material was discharged to obtain an antibacterial and antifungal component.

[0026] The samples were prepared by potassium bromide tableting method, and the antibacterial and antifungal components were tested by infrared spectrometer AVATAR-370FT. Figure 2 As shown in the figure, analysis shows that in the infrared spectrum of the antibacterial and antifungal components, 3054cm -1 The absorption peak of CH in olefins appeared at 3029 cm -1 The absorption peak of CH in the benzene ring appeared at 1733 cm -1 The absorption peak of C=O in the ester group appeared at 1649 cm -1 The absorption peak of C=O in amide appeared at 1560cm -1 The absorption peak of C=N appeared.

[0027] Example 1

[0028] Preparation of environmentally friendly materials Step 1, add 70g of polylactic acid, 20g of polycarbonate, 2g of ethylene-methyl acrylate-glycidyl methacrylate, 1g of polyethylene wax, 1g of antioxidant 1010, 3g of functional fiber filler, and 2g of antibacterial and mildew-proof components into a high-speed mixer, increase the temperature to 60°C, and mix for 1h to obtain a premix; Step 2: Place the premix in a twin-screw extruder, set the extrusion temperature to 180° C., the screw speed to 100 r / min, and melt-extrude and granulate to obtain an environmentally friendly material.

[0029] Example 2

[0030] Preparation of environmentally friendly materials Step 1: add 80g of polylactic acid, 30g of polycarbonate, 3g of ethylene-methyl acrylate-glycidyl methacrylate, 2g of polyethylene wax, 2g of antioxidant 1010, 4g of functional fiber filler, and 3g of antibacterial and mildew-proof component into a high-speed mixer, increase the temperature to 70°C, mix for 1.5h, and obtain a premix; Step 2: Place the premix in a twin-screw extruder, set the extrusion temperature to 190° C., the screw speed to 200 r / min, and melt-extrude and granulate to obtain an environmentally friendly material.

[0031] Example 3

[0032] Preparation of environmentally friendly materials Step 1: add 85g of polylactic acid, 40g of polycarbonate, 4g of ethylene-methyl acrylate-glycidyl methacrylate, 3g of polyethylene wax, 2.5g of antioxidant 1010, 5g of functional fiber filler, and 4g of antibacterial and mildew-proof component into a high-speed mixer, increase the temperature to 80°C, and mix for 2h to obtain a premix; Step 2: Place the premix in a twin-screw extruder, set the extrusion temperature to 200° C., the screw speed to 300 r / min, and melt-extrude and granulate to obtain an environmentally friendly material.

[0033] Example 4

[0034] Preparation of environmentally friendly materials Step 1: Add 90g of polylactic acid, 50g of polycarbonate, 5g of ethylene-methyl acrylate-glycidyl methacrylate, 4g of polyethylene wax, 3g of antioxidant 1010, 6g of functional fiber filler, and 5g of antibacterial and mildew-proof component into a high-speed mixer, increase the temperature to 90°C, and mix for 2h to obtain a premix; Step 2: Place the premix in a twin-screw extruder, set the extrusion temperature to 220° C., the screw speed to 400 r / min, and melt-extrude and granulate to obtain an environmentally friendly material.

[0035] Comparative Example 1 Preparation of environmentally friendly materials Step 1: Add 80g of polylactic acid, 30g of polycarbonate, 3g of ethylene-methyl acrylate-glycidyl methacrylate, 2g of polyethylene wax, 2g of antioxidant 1010, and 4g of functional fiber filler into a high-speed mixer, increase the temperature to 70°C, and mix for 1.5h to obtain a premix; Step 2: Place the premix in a twin-screw extruder, set the extrusion temperature to 190° C., the screw speed to 200 r / min, and melt-extrude and granulate to obtain an environmentally friendly material.

[0036] Comparative Example 2 Preparation of environmentally friendly materials Step 1, add 80g of polylactic acid, 30g of polycarbonate, 3g of ethylene-methyl acrylate-glycidyl methacrylate, 2g of polyethylene wax, 2g of antioxidant 1010, and 3g of antibacterial and mildew-proof components into a high-speed mixer, increase the temperature to 70°C, mix for 1.5h, and obtain a premix; Step 2: Place the premix in a twin-screw extruder, set the extrusion temperature to 190° C., the screw speed to 200 r / min, and melt-extrude and granulate to obtain an environmentally friendly material.

[0037] Comparative Example 3 Preparation of environmentally friendly materials Step 1, add 80g of polylactic acid, 30g of polycarbonate, 3g of ethylene-methyl acrylate-glycidyl methacrylate, 2g of polyethylene wax, 2g of antioxidant 1010, 4g of 2,2,6,6-tetramethyl-4-piperidinol, and 3g of antibacterial and mildew-proof components into a high mixer, increase the temperature to 70°C, mix for 1.5h, and obtain a premix; Step 2: Place the premix in a twin-screw extruder, set the extrusion temperature to 190° C., the screw speed to 200 r / min, and melt-extrude and granulate to obtain an environmentally friendly material.

[0038] Comparative Example 4 Preparation of environmentally friendly materials Step 1: Add 80g of polylactic acid, 30g of polycarbonate, 3g of ethylene-methyl acrylate-glycidyl methacrylate, 2g of polyethylene wax, 2g of antioxidant 1010, 4g of functional fiber filler, and 3g of diniconazole into a high-speed mixer, increase the temperature to 70°C, and mix for 1.5h to obtain a premix; Step 2: Place the premix in a twin-screw extruder, set the extrusion temperature to 190° C., the screw speed to 200 r / min, and melt-extrude and granulate to obtain an environmentally friendly material.

[0039] Performance Testing The environmentally friendly materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were prepared into samples that met the test conditions. According to the GB / T 1040.1-2018 standard, the tensile strength of the samples was tested to determine the mechanical properties of the samples. According to the GB / T 1043.2-2018 standard, the impact strength of the samples was tested to determine the impact toughness of the samples. The following method was used to test the UV resistance of the samples: According to the GB / T 16422.2-2022 standard, an FLB40T12E / 90D type UV fluorescent lamp was used. After aging for 500 hours, the formula △E=[(△L) 2 +(△a) 2 +(△b) 2 ] 1 / 2 The △E value of the color difference was calculated. The larger the △E value, the more serious the aging of the sample. The antibacterial and antifungal properties of the samples were tested by the following method: after the samples were placed for 60 days, 1 mL of Staphylococcus aureus was placed in a nutrient agar medium at 36 °C and cultured for 8 h. The bacterial solution was diluted to a concentration of 1 × 10 -5CFU / mL, take 1mL of bacterial solution and drop it on the surface of the sterilized sample, culture it at 36℃ for 6h, take 20μL of the cultured bacterial solution and evenly spread it on the solid culture medium. After culturing at 36℃ for 24h, count the number of colonies in the culture medium as W, and do a blank test at the same time, count the number of colonies in the blank test as X, and use the formula [(WX) / W]×100% to calculate the antibacterial rate. The test results are shown in the following table: Table 1

[0040] It can be seen from the above table that the environmentally friendly material prepared by the present invention has excellent mechanical properties, impact toughness, anti-ultraviolet properties and antibacterial and mildew-proof properties, among which the test effect of Example 2 is the best. Comparative Example 1 adds functional fiber filler, and has excellent mechanical properties and anti-ultraviolet properties. No antibacterial and mildew-proof component is added, and the impact toughness and antibacterial and mildew-proof properties are poor; Comparative Example 2 adds antibacterial and mildew-proof components, and has excellent impact toughness and antibacterial and mildew-proof properties. No functional fiber filler is added, and the anti-ultraviolet properties and mechanical properties are poor; Comparative Example 3 adds 2,2,6,6-tetramethyl-4-piperidinol and antibacterial and mildew-proof components, and small molecule hindered amine 2,2,6,6- Tetramethyl-4-piperidinol may migrate and precipitate, resulting in poor anti-ultraviolet performance, but excellent impact toughness and antibacterial and mildew proof properties. Without the addition of quartz fiber, the mechanical properties of the polylactic acid matrix cannot be enhanced, so the mechanical properties are poor; Comparative Example 4 adds functional fiber filler and diniconazole, and has excellent anti-ultraviolet and mechanical properties, but due to the migration and precipitation of small molecule antibacterial and mildew proof diniconazole, it leads to poor antibacterial and mildew proof properties, and it is impossible to utilize the branched structure of polyamidoamine to interact with the polylactic acid matrix, entangle with the polylactic acid molecular chains, enhance the density of the polylactic acid matrix molecular chains, and improve the impact toughness, so the impact toughness is poor.

[0041] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. An environmentally friendly material for outdoor seating, characterized in that: The invention comprises the following raw materials in parts by weight: 70-90 parts of polylactic acid, 20-50 parts of polycarbonate, 2-5 parts of a compatibilizer, 1-4 parts of a lubricant, 1-3 parts of an antioxidant, 3-6 parts of a functional fiber filler and 2-5 parts of an antibacterial and anti-mildew component.

2. The environmentally friendly material for outdoor seats according to claim 1, characterized in that: The compatibilizer is ethylene-methyl acrylate-glycidyl methacrylate; the lubricant is polyethylene wax; and the antioxidant is antioxidant 1010 or antioxidant 168.

3. The environmentally friendly material for outdoor seats according to claim 1, characterized in that: The method for preparing the functional fiber filler comprises the following steps: S1. Mix quartz fiber with N,N-dimethylformamide, raise the temperature to 60-80°C, add chloroethyl isocyanate and catalyst A, react for 2-4 hours, filter, wash and dry to obtain modified quartz fiber; S2. Add the modified quartz fiber into toluene, mix well, introduce nitrogen, raise the temperature to 70-80°C, add 2,2,6,6-tetramethyl-4-piperidinol and an alkaline catalyst, react for 3-5 hours, filter, wash and dry to obtain a functional fiber filler.

4. The environmentally friendly material for outdoor seats according to claim 3, characterized in that: In S1, the catalyst A is dibutyltin dilaurate or stannous octoate.

5. The environmentally friendly material for outdoor seats according to claim 3, characterized in that: In S2, the alkaline catalyst is a sodium carbonate solution or a potassium carbonate solution.

6. The environmentally friendly material for outdoor seats according to claim 1, characterized in that: The preparation method of the antibacterial and mildew-proof component is as follows: Add polyamide amine to toluene and stir evenly, add anhydride modifier, react at room temperature for 1-3 hours, then increase the temperature to 80-100°C, add diniconazole and catalyst B, keep the temperature for 3-5 hours, cool to room temperature, discharge and obtain antibacterial and antifungal components.

7. The environmentally friendly material for outdoor seats according to claim 6, characterized in that: The acid anhydride modifier is succinic anhydride or glutaric anhydride.

8. The environmentally friendly material for outdoor seats according to claim 6, characterized in that: The catalyst B is p-toluenesulfonic acid.

9. A production process of environmentally friendly materials for outdoor seats as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Add polylactic acid, polycarbonate, compatibilizer, lubricant, antioxidant, functional fiber filler, and antibacterial and mildew-proof components into a high-speed mixer, raise the temperature to 60-90° C., and mix for 1-2 hours to obtain a premix; Step 2: placing the premix in a twin-screw extruder, and performing melt extrusion and granulation to obtain an environmentally friendly material.

10. The production process of environmentally friendly materials for outdoor seats according to claim 9, characterized in that: In step 2, the extrusion temperature of the twin-screw extruder is 180-220° C., and the screw speed is 100-400 r / min.

Citation Information

Patent Citations

  • Polyactic acid / polycarbonate alloy material, and preparation method and application thereof

    CN102020834A

  • Degradable PC (Poly Carbonate) / PLA (Poly Lactic Acid) alloy and preparation method thereof

    CN102653627A

  • Plastic composition, plastic and preparation method of the plastic

    CN102850744A

  • Scratch-resistant polycarbonate / polylactic acid alloy material and preparation method thereof

    CN104086968A

  • Polylactic acid / PC (polycarbonate) alloy containing biodegradable material and preparation method thereof

    CN106496988A